Alveolar bone density based on image density of intraoral radiography using artificial intelligence software: Cases of osteoporosis patients with antiresorptive medications administration before tooth extraction - Eizaburo Kobayashi; Yoshiyuki Minami; Ruri Ogawa; Yasuhito Tezuka; Ichiro Ogura (Wolters Kluwer Medknow Publications, 2022)
Background: In recent years, an artificial intelligence (AI) software "DentalSCOPE" for alveolar bone density based on image density of intraoral radiography was developed. Aims: The purpose of this study was to evaluate the alveolar bone density of osteoporosis patients with antiresorptive medications administration before tooth extraction using DentalSCOPE. Materials and Methods: Five osteoporosis patients with antiresorptive medications administration before tooth extraction were analyzed using a computer program "DentalSCOPE" for alveolar bone density based on image density of intraoral radiography. The alveolar bone density around extraction tooth was compared to lytic and sclerotic bone reaction with the opposite side as normal region. Statistical analyses of alveolar bone density were performed with Wilcoxon rank-sum test. P < 0.05 was considered statistically significant. Results: The alveolar bone density of the opposite side as normal region (972.9 ± 74.3 mg/cm2) was significantly higher than those of lytic bone reaction (633.9 ± 114.2 mg/cm2, P = 0.043) and lower than those of sclerotic bone reaction (1144.0 ± 99.4 mg/cm2, P = 0.043). Conclusions: This study evaluated the alveolar bone density of osteoporosis patients with antiresorptive medications administration before tooth extraction using DentalSCOPE and indicated that the computer program could be useful for the evaluation of osteoporosis patients.